60 minutes. City within a city / produced by Michael Radutzky, Tanya Simon. - Bradley, Ed, 1941-2006; Radutzky, Michael; Simon, Tanya (60 Minutes: 1997-2014, 2001)
This segment examines the work of the volunteers who supported the rescue efforts at ground zero. Ed Bradley reports.